Twenty-One Years of Staphylococcus aureus Bacteremia (SAB): Variations in Bacterial Genotype and Clinical Phenotype in the S. aureus Bacteremia Group Prospective Cohort Study (SABG-PCS) from 1995 to 2015. (4th October 2017) - Souli, Maria; Ruffin, Felicia; Park, Lawrence; Sharma-Kuinkel, Batu K; Thaden, Joshua T; Maskarinec, Stacey; Gao, Shengli; Lent, Nicholas Christopoulos; Wanda, Lisa; Hill-Rorie, Jonathan; Warren, Bobby; Hansen, Brenda; et al.
Abstract: Background: Using the SABG-PCS, we aimed to identify possible temporal variations in the clinical phenotype and bacterial genotype of SAB in a single academic medical center from Jan 1, 1995 to Dec 31, 2015. Methods: SABG-PCS prospectively enrolled all eligible adult hospitalized non-neutropenic patients with monomicrobial SAB at Duke U Med Center (DUMC). Demographic, clinical and outcome data were collected. The initial bloodstream S. aureus isolate from each subject was genotyped using spa typing. Clonal Complex (CC) was inferred using eGenomics software. Proportions of complications and CC were calculated overall and by calendar year. Secular trends in proportions were estimated with linear regression. Results: Among 2, 179 unique patients admitted to DUMC with SAB during the study period, 57% were male, and the mean age was 58y. Common comorbidities included end stage renal disease (21.4%), diabetes mellitus (38.1%), and injection drug use (4.5%). Most SAB was community-acquired health-care associated (CA-HCA; 58.8%), followed by hospital-acquired (HA; 34%). Over the course of the study, annual rates increased for CA-HCA SAB (1.3% P < 0.0001) but decreased for HA SAB (-2.1%, P < 0.0001). Although significant annual increases were noted in the overall rate of metastatic complications (0.91%, P = 0.028), including abscesses (0.44%, P = 0.004), vertebral osteomyelitis (0.26%, P = 0.003), and septic emboli (0.63%, P < 0.0001) (Figure 1 ), rates of endocarditis did not change significantly (0.36%, P = 0.101). Bacterial genotype also shifted during the study period, with annual changes in prevalence of CC30 (-1.3%, P = 0.0002), CC5 (7.5%, P = 0.104) and CC8 (1.4%, P < 0.0001) (Figure 2 ). Patients with SAB due to CC8 were significantly more likely to develop metastatic complications in general (RR 1.33, 95% CI 1.17–1.51), and metastatic abscess (RR 2.13, 95% CI 1.55–2.93) and septic emboli (RR 1.94, 95% CI 1.31–2.89) in particular. Conclusion: Clinical phenotype and bacterial genotype of SAB in our study cohort changed significantly over the past 21 years. The rise of CC8 in SAB was associated with increased rates of complications in general and abscess in particular. By contrast, rates of endocarditis have remained stable irrespective of genotype distribution. Disclosures: V. Fowler Jr., Pfizer, Novartis, Galderma, Novadigm, Durata, Debiopharm, Genentech, Achaogen, Affinium, Medicines Co., Cerexa, Tetraphase, Trius, MedImmune, Bayer, Theravance, Cubist, Basilea, Affinergy, Janssen, xBiotech, Contrafect: Consultant, Consulting fee; NIH, MedImmune, Cerexa/Forest/Actavis/Allergan, Pfizer, Advanced Liquid Logics, Theravance, Novartis, Cubist/Merck; Medical Biosurfaces; Locus; Affinergy; Contrafect; Karius: Grant Investigator, Grant recipient; Green Cross, Cubist, Cerexa, Durata, Theravance; Debiopharm: Consultant, Consulting fee; UpToDate: Royalties, Royalties